2018
DOI: 10.21061/jte.v29i2.a.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Integrative STEM Education: Teacher and Administrator Professional Development

Abstract: The integration of science, technology, engineering, and mathematics (STEM) education, also referred to as integrative STEM education, is a relatively new interdisciplinary teaching technique that incorporates an engineering design-based learning approach with mathematics, science, technology, and engineering education (Sanders, 2010, 2012, 2013; Wells, 2010, 2013). Over the past 11 years, 475 teachers and administrators, representing kindergarten through eighth grade teachers and elementary school administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 4 publications
1
33
0
2
Order By: Relevance
“…Even students and teachers think that STEM is essential in future career development. During STEM-EDP learning in the given problems (Havice et al 2018), students work in groups to develop their skills and creativity (Havice et al 2018;Meyrick, 2011), the learning teacher plays a role in the achievement of learning objectives. STEM-EDP provides a useful learning environment (Avery & Reeve, 2013), in developing students' reasoning skills, critical thinking skills, creativity, and innovation.…”
Section: Stem-edp Leaf Plot and Summative Leaf Plot Testmentioning
confidence: 99%
“…Even students and teachers think that STEM is essential in future career development. During STEM-EDP learning in the given problems (Havice et al 2018), students work in groups to develop their skills and creativity (Havice et al 2018;Meyrick, 2011), the learning teacher plays a role in the achievement of learning objectives. STEM-EDP provides a useful learning environment (Avery & Reeve, 2013), in developing students' reasoning skills, critical thinking skills, creativity, and innovation.…”
Section: Stem-edp Leaf Plot and Summative Leaf Plot Testmentioning
confidence: 99%
“…Integrative science, technology, engineering, and mathematics (I-STEM) education provides direction for teaching, leading, and learning practices related to students' abilities to identify, think critically about, and propose solutions to real-world problems. However, many educators are unfamiliar with the conceptualization and praxis of I-STEM curricula (Havice, Havice, Waugaman, & Walker, 2018;Herro & Quigley, 2017). School program leaders cultivating an I-STEM culture also encounter difficult challenges such as reorganizing STEM subjects for greater integration and fostering teacher's knowledge, confidence, and pedagogical practice (Shernoff, Sinha, Bressler, & Ginsburg, 2017;Nadelson & Seifert, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although effective models of I-STEM education are still emerging (LaForce, Noble, King, Holt, & Century, 2014), positive outcomes in administrator and teacher praxis are evident. Professional development (PD) programs have been shown to significantly increase teacher and administrator self-efficacy in problem-and project-based learning (Havice et al, 2018), teacher collaborative efforts and educational technology use (Herro & Quigley, 2017), mathematics achievement (Burghardt, Hecht, Russo, Lauckhardt, & Hacker, 2010), and teacher involvement in community engagement (Havice, 2015). However, it is important to note that the catalysts for transformative paradigms and praxis are school administrators and teacher leaders.…”
Section: Note: This Article Was Based On the First Author's Dissertatmentioning
confidence: 99%
“…This can only be realized if the learners are enjoying their works independently or collaboratively. Havice et al (2018) found that poor study habit added with the spoon-feeding done by the teachers make them more passive. In addition, learners do not actively participate in the accomplishment of inquiry skills activities due to absence of interest, motivation, and enthusiasm.…”
Section: Part a Teachers' And Learners' Responses On The Causes Of Difficulties In Science Inquiry Skills Enrichmentmentioning
confidence: 99%